2021
DOI: 10.1080/19490976.2021.1897209
|View full text |Cite
|
Sign up to set email alerts
|

The high prevalence of Clostridioides difficile among nursing home elders associates with a dysbiotic microbiome

Abstract: Clostridioides difficile disproportionally affects the elderly living in nursing homes (NHs). Our objective was to explore the prevalence of C. difficile in NH elders, over time and to determine whether the microbiome or other clinical factors are associated with C. difficile colonization. We collected serial stool samples from NH residents. C. difficile prevalence was determined by quantitative polymerase-chain reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…S3) we fit the model NES s , i ~ f (TTP, X ) i + 1∣ID , where NES is the normalized enrichment score for hallmark pathway (or signature) s in sample i , f is a general nonlinear function (the random forest) applied to TTP and species relative abundances X in sample i as fixed effects, and 1|ID indicates the random effect to account for multiple samples from the same patient. To determine the significance of model-inferred associations, we used permutated importance analysis ( 44 ). For the significant associations obtained from the permutated importance calculations (FDR < 0.1), we then applied univariate linear mixed-effects models to determine the directionality (positive/negative) of the association.…”
Section: Resultsmentioning
confidence: 99%
“…S3) we fit the model NES s , i ~ f (TTP, X ) i + 1∣ID , where NES is the normalized enrichment score for hallmark pathway (or signature) s in sample i , f is a general nonlinear function (the random forest) applied to TTP and species relative abundances X in sample i as fixed effects, and 1|ID indicates the random effect to account for multiple samples from the same patient. To determine the significance of model-inferred associations, we used permutated importance analysis ( 44 ). For the significant associations obtained from the permutated importance calculations (FDR < 0.1), we then applied univariate linear mixed-effects models to determine the directionality (positive/negative) of the association.…”
Section: Resultsmentioning
confidence: 99%
“…The  datasets highlighted that performing change analyses can produce unique insights compared to using Original longitudinal data without  calculations. Several studies have applied MERFs for feature selection 41,42 , however, they did not use s, which could lead to a possible loss of valuable insights.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, residents of an elderly nursing home in America consuming a typical low-fibre-nursing-home diet had lower levels of butyrate producers and greater abundances of dysbiotic species [184]. A more recent study by the same group revealed that the dysbiotic gut microbiota of elderly nursing home residents -characterised by pro-inflammatory bacteria and reduced anti-inflammatory microbes -associated with C. difficile colonization [185].…”
Section: Factors That Influence the Elderly Gut Microbiotamentioning
confidence: 98%
“…The resulting decrease in microbiota diversity and the elimination of health-associated taxa enable C. difficile to become established in the gut [188]. Yet, as previously mentioned, the dysbiotic microbiota of elderly nursing home residents also allows C. difficile to flourish [185]. CDI in hospitalised elderly individuals was also associated with under-representation of gut microbes with potential protective properties including Bacteroides, Alistipes, Lachnospira, and Barnesiella, and overrepresentation of opportunistic pathogens including Klebsiella, Escherichia/Shigella, Sutterella, Enterococcus, Citrobacter, Veillonella, Proteus, Helicobacter, Morganella, Hafnia, Corynebacterium and Staphylococcus [189].…”
Section: Clostridioides Difficile Infectionmentioning
confidence: 99%